Liquid-gas phase transition in Bose-Einstein condensates with time evolution - Gammal, A. [UNESP]; Frederico, T.; Tomio, Lauro [UNESP]; Chomaz, Ph. (American Physical Society (APS), 2000)
We study the effects of a repulsive three-body interaction on a system of trapped ultracold atoms in a Bose-Einstein condensed state. The stationary solutions of the corresponding s-wave nonlinear Schrödinger equation suggest a scenario of first-order liquid-gas phase transition in the condensed state up to a critical strength of the effective three-body force. The time evolution of the condensate with feeding process and three-body recombination losses has a different characteristic pattern. Also, the decay time of the dense (liquid) phase is longer than expected due to strong oscillations of the mean-squared radius. © 2000 The American Physical Society.